Life satisfaction and problem-focused coping among future physical culture teachers - Oleksandr Kholodny; Volodymyr Prystynskyi; Anton Biryukov; Katarzyna Prusik (Pedagogy of Health)
Background and Study Aim. Behavior adjustment, as an individual's response to threats, is an effective means of managing stress. Therefore, the aim of this study is to explore the correlation between life satisfaction and problem-focused coping strategies among future physical culture teachers.